2022
DOI: 10.1186/s12981-022-00482-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antiretroviral therapy (ART) duration on ART adherence among men who have sex with men (MSM) living with HIV in Jinan of China

Abstract: Background Consistent and complete adherence is considered an essential requirement for patients on antiretroviral therapy (ART). This study aimed to evaluate the impact of ART duration on ART adherence, identify the trend of complete adherence, and compare the factors associated with ART adherence between short-term and long-term ART group among men who have sex with men (MSM) living with HIV in Jinan of China. Methods MSM living with HIV aged 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(36 reference statements)
0
6
0
Order By: Relevance
“… 44 46 However, a large Nigerian study 47 reported associations between longer duration of ART and risk of low-level viraemia, which is similar to our findings. This may be a result of declining ART adherence over time, which has been linked to longer ART duration, 48 , 49 even among members of adherence clubs, 50 and points to the need for continuous person-centred adherence support with increasing ART duration. Previous research has also associated longer ART duration with mental health issues, 51 which may consequently impact ART adherence adversely, 52 , 53 and this underscores the need to integrate mental health services with adherence counselling 54 for individuals with low-level viraemia.…”
Section: Discussionmentioning
confidence: 99%
“… 44 46 However, a large Nigerian study 47 reported associations between longer duration of ART and risk of low-level viraemia, which is similar to our findings. This may be a result of declining ART adherence over time, which has been linked to longer ART duration, 48 , 49 even among members of adherence clubs, 50 and points to the need for continuous person-centred adherence support with increasing ART duration. Previous research has also associated longer ART duration with mental health issues, 51 which may consequently impact ART adherence adversely, 52 , 53 and this underscores the need to integrate mental health services with adherence counselling 54 for individuals with low-level viraemia.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the association we found between social support and ART adherence/retention is driven by how we conceptualized it. Additionally, data on “duration on ART” was not collected and yet it is known to influence ART adherence [ 38 ]. The study relied on self-reported data other than hospital records, hence there is the possibility that the data was affected by some biases such as social desirability bias.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that longer treatment duration leads to better quality of life; hence patients become more motivated to follow healthcare providers’, advice including adhering to their medications [ 39 ]. In contrast, a study in Eastern China found men with longer ART duration were less likely to be adherent [ 40 ].…”
Section: Discussionmentioning
confidence: 99%